Effects of UAV mobility patterns on data collection in wireless sensor networks - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2015)
Sensor nodes in a Wireless Sensor Network (WSN) can be dispersed over a remote sensing area e.g. the regions that cannot be accessed by human beings (inaccessible regions). In such kind of networks, data collection becomes one of the major issues. Getting connected to each sensor node and retrieving the information in time introduces new challenges. Mobile sink usage, especially the Unmanned Aerial Vehicle (UAV), is the most convenient approach to cover the area and access each sensor node in such a large scale WSN. However, the operation of the UAV depends on some parameters such as endurance time, altitude, speed, radio type in use, and the path. In this paper, we explore various mobility patterns of UAV that follow different paths to sweep the playground in order to seek the best area coverage with maximum number of covered nodes in less amount of time needed by the mobile sink. A realistic simulation environment is used in order to compare and evaluate the performance of the system. We present the performance results for the explored UAV mobility patterns. The results are very useful to present the tradeoff between maximizing the covered nodes and minimizing the operation time for choosing the appropriate mobility pattern. © 2015 IEEE.